Pengaruh Model Pembelajaran Inkuiri Berisi STEAM untuk Meningkatkan Keterampilan Proses Sains - Nesya Pramitasari; Purwanti Widhy Hastuti; Rizki Arumning Tyas; Putri Anjarsari; Ekosari Roektiningroem (Postgraduate, University of Mataram, 2024)
Science process skills as an approach is very important, due to it fosters experience in science learning process. This study aims to analyze the influence of STEAM-based inquiry learning models on students' science process skills. The type of research used is experimental research. The research design used is a quasi-experiment with a nonequivalent control group design. The research data were collected using test techniques using pretest and posttest questions of science process skills, non-test techniques in the form of observation sheets of learning implementation, and observation sheets of science process skills. The data analysis technique used was percentage analysis of the learning implementation sheet and science process skills observation sheet, hypothesis prerequisite test in the form of normality test and homogeneity test, hypothesis testing with independent sample t-test, and effect size test. The results of the independent sample t-test test have a significance value of 0.013 <0.05, which shows a significant difference between the experimental and control classes. The magnitude of the treatment effect is measured by the effect size test, resulting in a value of 0.642, which is included in the strong category. Based on the analysis results, it can be concluded that the STEAM-based inquiry learning model significantly affects students' science process skills.